Unveiling the Complexities of ESG and CSR Disclosures Determinants: A Systematic Literature Review - Seow, Richard (Journal of Technology Management and Business, 2024)
As the focus on environmental, social, and governance (ESG) and corporate social responsibility (CSR) intensifies within the private sector to advance sustainability, studies exploring the determinants of these disclosure practices have attracted considerable scholarly interest over the past decade. Despite notable similarities between ESG and CSR, the somewhat murky relationship between the two has introduced significant ambiguities into the academic discourse. This study identified 164 articles from the Web of Science (WoS) and Scopus databases for systematic review, indicating post-2018 articles to constitute 70% and 81% concentrating on the extent of disclosures. Legitimacy theory, stakeholder theory, and agency theory were the theoretical frameworks commonly cited in the literature. Various country, industry, firm, and individual-level determinants were discovered in the literature. There remains considerable confusion in the literature concerning the definitions and proxies used for CSR disclosures which future research can address. The study offers insightful clarity to the burgeoning knowledge of ESG and CSR.